THE INFLUENCE OF PATIENT EXPERIENCE, ACCESSIBILITY, BRAND IMAGE ON THE INTEREST OF REPEAT VISITS OF MERIAL TOWER INPATIENTS AT PELNI HOSPITAL - Ruth Novia Elnasanti; Rian Adi Pamungkas; Intan Silviana Mustikawati; Rokiah Kusumapradja (Jurnal Cinta Nusantara, 2025)
Revisit intention can be interpreted as the patient's attitude in deciding whether the hospital will be chosen again for health activities. Many variables influence revisit intention, but in this study the variables are limited to patient experience, accessibility, and brand image. The purpose of this study was to analyze partially and simultaneously the influence of patient experience, accessibility, and brand image on the revisit intention of inpatients at Merial Tower, Pelni Hospital. This study was conducted using a quantitative analysis method on a population of 125 Merial Tower inpatients at Pelni Hospital. From this population, a purposive sampling technique was used to determine the number of samples to be studied, which was 95 samples. Questionnaires were distributed to all samples, and the results were analyzed using SPSS 24. Based on the test results, it was found that patient experience, accessibility, and brand image had a significant simultaneous effect on the revisit intention of Merial Tower inpatients at Pelni Hospital. Partially, patient experience, accessibility, and brand image were each found to have a positive effect on the revisit intention of Merial Tower inpatients at Pelni Hospital. Keywords: Patient Experience, Accessibility, Brand Image, Revisit Interest